An updated phylogeny of Anisoptera including formal convergence analysis of morphological characters. (5th May 2013) - BLANKE, ALEXANDER; GREVE, CAROLA; MOKSO, RAJMUND; BECKMANN, FELIX; MISOF, BERNHARD
Abstract Family interrelationships among Anisoptera (dragonflies) are unresolved. Molecular markers applied thus far have not been particularly useful for resolving relationships at the family level. Previous morphological studies have depended heavily on characters of wing venation and articulation which are believed to display considerable degrees of homoplasy due to adaptations to different flight modes. Here, we present a comprehensive anatomical dataset of the head morphology of Anisoptera focusing on muscle organization and endoskeletal features covering nearly all families. The characters are illustrated in detail and incorporated into an updated morphological character matrix covering all parts of the dragonfly body. Phylogenetic analysis recovers all families as monophyletic clades except Corduliidae, Gomphidae as sister group to all remaining Anisoptera, and Austropetaliidae as sister group to Aeshnidae (=Aeshnoidea). The position of Petaluridae and Aeshnoidea to each other could not be resolved. Libelluloidea is monophyletic with Neopetalia and Cordulegastridae as first splits. Chlorogomphidae is sister to monophyletic [Synthemistidae + ('Corduliidae' + Libellulidae)]. In addition, we applied a recently published formal approach to detect concerted convergence in morphological data matrices and uncover possible homoplasies. Analyses show that especially head and thorax characters may harbour homoplasies. After exclusion of possible homoplastic characters, Gomphidae is corroborated as sister group to all remaining Anisoptera.